SYNTHESIS DIBENZIL IS REGISTERED THROUGH THE POLYMERIZED POLYMERYLENE AS ALTERNATIVE RECYCLE PLASTIC RECYCLE - Suwardi Suwardi; Crys Fajar Partana; Agus Salim (Jurnal Penelitian Saintek, 2005)
Synthesis  dibenzyl terephathalate were done through PET softdrinkbottles   degradation   by   refluxing   in   benzyl   alcohol   at   14~C temperature for 20, 24. and 28 hours in the presence  of zinc acetate catalyst. The result of degradation was purified  by recristalization in methanol and then melting point  (mp), FTIR, I H NMR spectra, and TLC spot were determined. The melting point of product degradation.for   28   hours  was  98-99  "c.  Based   FTIR  spectra   known  thatcompounds  of  product   degradation  have   OH,  C=O,  C-O,  CH,monosubstituted benzene, disubstituted benzene groups,  while on IH NMR spectra showed chemical shift at 8.2 ppm  (s, IO H of monosubtituted benzene), 7.5 ppm (s, 9 H consist of 4 H disubstituted benzene and 5 H of aromatic benzyl alcohol), 5.4 ppm  (s, 1 H from OH benzyl alcohol), 4.8 ppm (s, 4 H of methylene), and 2.9 ppm (s. 7H of other traces). The single spot ofTLC plate indicated that productdegradation for  28 hours might be a single compound. Based these characterization  concluded  that  compound  of product  degradation was dibenzyl terephthalate contains benzyl alcohol and other traces.